2018
DOI: 10.1186/s12883-018-1061-0
|View full text |Cite|
|
Sign up to set email alerts
|

Case series of Creutzfeldt-Jakob disease in a third-level hospital in Quito

Abstract: BackgroundCreutzfeldt-Jakob disease is a rare and fatal neurodegenerative disorder that affects mammals and humans. The prevalence of this disease in the United States is 0.5 to 1 per million inhabitants. So far in Ecuador, we do not know what the prevalence or incidence is, and only one case report has been written.Case presentationWe present a case series of Creutzfeldt-Jakob disease in a third-level hospital in Quito. The average age of symptom onset in our patients was 58.8 years. The male to female ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…Among the countries of Middle and South America, some such as Argentina, Chile, Mexico, Brazil, and Peru have reported their data of PrD surveillance or studies. For (49,50). It is apparent that the PrD or CJD case numbers globally are markedly undervalued, which may pose a potential biosafety risk.…”
Section: Discussionmentioning
confidence: 99%
“…Among the countries of Middle and South America, some such as Argentina, Chile, Mexico, Brazil, and Peru have reported their data of PrD surveillance or studies. For (49,50). It is apparent that the PrD or CJD case numbers globally are markedly undervalued, which may pose a potential biosafety risk.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that approximately one-third of sCJD cases initially present with cognitive or behavioral changes, and close to one-third have cerebellar ataxia, aphasia, visual dysfunction, and motor deficit as the initial presenting symptoms. Depression has also been found in some patients with CJD [11]. Myoclonus can sometimes be absent initially, but present in the advanced stages of sCJD [12].…”
Section: Discussionmentioning
confidence: 99%
“…La ECJ se caracteriza por tener una presentación clínica heterogénea donde el síntoma cardinal es la demencia de curso rápidamente progresivo, asociado a síntomas constitucionales inespecíficos (compromiso del estado general, baja de peso, alteraciones del sueño), síntomas neuropsiquiátricos (depresión, irritabilidad, agresividad, apatía, cambios de personalidad) y síntomas neurológicos variados que revelan el depósito de la proteína priónica anormal en diferentes localizaciones del encéfalo 4,15 . Los hallazgos clínicos neurológicos que más comúnmente hacen sospechar esta enfermedad son las alteraciones de funciones cerebrales superiores, las mioclonías y la ataxia 16 , los cuales son los síndromes más frecuentemente encontrados en nuestra serie al momento de la consulta.…”
Section: Discussionunclassified